Thermal properties of PLA/kenaf green nanocomposite: Effect of chemi-mechanical treatment - Wan Jaafar, Wan Nor Raihan; Surip, S. N.; Azmi, Nur Naziha; Bonnia, N. N.; Anuar, Hazleen; H. Noor, Azlina; Abd. Razak, S. B. (Trans Tech Publications, 2012)
This study was conducted to produce green composite from kenaf with better thermal properties. Kenaf fibre was successfully prepared by chemi-mechanical method. Kenaf fibre was firstly treated with sodium hydroxide (NaOH) at 6% w/w followed by acidic treatment with different concentrations (0.5M, 1.0M and 1.5M). The PLA/kenaf nanofibre composites were referred as KC0.5, KC1.0 and KC1.5 according to acid concentration used. Differential scanning calorimetry (DSC) was done to investigate thermal properties of the composites. The glass transition, crystallization and melting temperature shows similar trend where 1.0M treated fibre composites gives better thermal properties than 0.5M and 1.5M treated fibre composites. Transmission electron microscopy (TEM) micrographs suggested the nanofibre dispersion in mixed-pattern; exfoliation and small agglomeration.